Tell me who you go with and I will tell you what you do: Antarctic seal lice behave differently - Soto, Florencia Anabella; Crespo, José Emilio; Negrete, Javier; Leonardi, María Soledad (Marine Biology)
Lice of the family Echinophthiriidae are obligate and permanent ectoparasites of pinnipeds and sea otters. Morphological, ecological, and behavioral adaptations have enabled them to survive in their amphibian hosts. However, it has been shown experimentally that the eggs do not survive submerged. This physiological limitation restricts their reproductive events to the terrestrial periods of their hosts, mainly during molting and reproduction. We studied the reproductive strategies of Antarctophthirus lobodontis on crabeater seals (CS, n = 54) and A. carlinii on Weddell seals (WS, n = 54) from Danco Coast, Antarctic Peninsula, during the molting season. Lice were sexed and classified as adults or nymphs under a stereomicroscope. The 20.37% of the CS had potentially viable eggs and all the nymphal stages and adults. However, in the WS, we only found N3 and adults. Our results would suggest that A. lobodontis lays viable eggs that can survive immersion.Instead, the transmission of A. carlinii would be mainly by adults. According to previous studies, A. carlinii would reproduce during the reproductive season of WS. These reproductive strategies of seal lice would be related to the life history of their host, mainly to diving behavior and the haul-out patterns during their life cycle, reflecting the strong co-adaptation and co-evolution mechanisms between seals and lice. The differences in the population structure of the two species observedhere may indicate that they are different species, or at least that they have undergone different co-evolutionary processes depending on the habit of their hosts. Fil: Soto, Florencia Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Crespo, José Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos ...